The History and Development of HER2 Inhibitors - Xiaohui Xia; Chen Gong; Yinan Zhang; Huihua Xiong (MDPI AG, 2023)
HER2 is highly expressed in a variety of malignant tumors and affects the prognosis of patients, making it a highly sensitive target for cancer therapy. Since the approval of the first HER2 inhibitor, trastuzumab, in 1998, HER2-targeted drugs have rapidly evolved. Currently, targeting HER2 drugs mainly include monoclonal antibodies (mAbs), tyrosine kinase inhibitors (TKIs), and antibody-drug conjugates (ADCs). This article reviews the development of HER2 inhibitors for various tumors over the past 20 years.